2012
DOI: 10.1111/j.1574-6968.2012.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

Small non-coding RNA SraG regulates the operon YPK_1206-1205 in Yersinia pseudotuberculosis

Abstract: Small non-coding RNAs (sRNAs) are important post-transcriptional regulators in prokaryotes and have been demonstrated to participate in most of the cellular processes. SraG is an sRNA found in several enterobacterial species, but its targets have not been characterized. Here, we compared the protein expression patterns between the wild-type and an sraG-depleted mutant of Yersinia pseudotuberculosis by proteomic analysis. Sixteen proteins were up- or downregulated, and the negative regulatory role of SraG assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The function of SraG was studied in Yersinia pseudotuberculosis. While no effect on pnp was reported, SraG was shown to negatively regulate the YPK_1206-1205 operon, which encodes genes that have no homologs outside the Yersinia genus (Lu et al 2012). Other potential candidates were identified by proteomic analysis of the wt and ΔsraG mutant in this species but without further confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of SraG was studied in Yersinia pseudotuberculosis. While no effect on pnp was reported, SraG was shown to negatively regulate the YPK_1206-1205 operon, which encodes genes that have no homologs outside the Yersinia genus (Lu et al 2012). Other potential candidates were identified by proteomic analysis of the wt and ΔsraG mutant in this species but without further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…SraG of Yersinia pseudotuberculosis has been shown to regulate the YPK_1206-1205 operon (Lu et al 2012). We investigated a possible role of SraG on RNA targets transcribed from elsewhere on the E. coli chromosome by using various strategies.…”
Section: Does Srag Have Any Other Roles?mentioning
confidence: 99%
“…Naturally occurring antisense small noncoding RNAs (sRNA) have been reported to repress genes downstream of the targeted ORF. Two examples are sRNAs of the phoPQ operon in E. coli (37) and the YPK_1206-1205 operon in Yersinia pseudotuberculosis (38), where sRNAs silence the target and downstream genes. It will be interesting to see if upstream silencing exists in nature as more sRNAs are identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences within the coding region of YPK_1206 are necessary and sufficient for negative regulation of both YPK_1206 and the downstream YPK_1205. 36 Although a direct binding site between SraG and YPK_1206-1205 has not been identified, truncation analyses revealed that a region between +9-+63 of the YPK_1206 coding region is required for coordinate regulation of the operon. 36 Whether SraG affects only translation or both translation and mRNA stability by binding at one site is currently unknown.…”
Section: New Developments In Post-transcriptional Regulation Of Operomentioning
confidence: 99%
“…35 While very little is known about the physiological function of SraG, a recent study showed that Yersinia pseudotuberculosis SraG regulates a polycistronic mRNA, YPK_1206-1205. 36 While the functions of the YPK_1205 and the iscS, iscU and iscA genes encode the biogenesis and assembly machinery, IscR is a transcription factor and autorepresses iscRSUA. 31 IscR exists in the Holo-form bound by Fe-S clusters or in the unbound Apo-form.…”
Section: New Developments In Post-transcriptional Regulation Of Operomentioning
confidence: 99%